2021
DOI: 10.3390/ani11071879
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Creatine Kinase and Aspartate Aminotransferase for Monitoring Muscle Effort in Working Dogs in Different Simulated Fieldworks

Abstract: The clinical profiles of muscle biomarkers (Creatine Kinase–CK-and Aspartate Aminotransferase–AST) performed during training may help in determining the fitness level of dogs and their potentiality to perform specific activities. This study investigated the potential variations of physiological parameters and muscular biomarkers in trained search and rescue dogs during search activity in two different areas. The aim was to verify the absence of any muscular enzymes after 20 min of search activity. The variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Thus, higher concentrations at the beginning might reflect work activities, which then declined. This result agrees with human studies showing physical inactivity can reduce serum CK concentrations ( 20 , 21 , 29 , 30 ). Of note was one camp with no change in CK concentrations (Camp F) that did not alter walking distance or chain hours, while two camps (Camp B and Camp D) that walked elephants the most before COVID-19 had higher initial values, which then declined.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, higher concentrations at the beginning might reflect work activities, which then declined. This result agrees with human studies showing physical inactivity can reduce serum CK concentrations ( 20 , 21 , 29 , 30 ). Of note was one camp with no change in CK concentrations (Camp F) that did not alter walking distance or chain hours, while two camps (Camp B and Camp D) that walked elephants the most before COVID-19 had higher initial values, which then declined.…”
Section: Discussionsupporting
confidence: 92%
“…The reference range for serum CK in Asian elephants is 50–250 U/L ( 22 ), which is overall lower than that noted in this study (196.7–387.3 U/L). This enzyme is found in muscles and regarded as an indicator of cell activity, with increases associated with exercise ( 23–26 ), muscle damage ( 27 , 28 ), and inflammation or trauma ( 29 , 30 ). In this study, CK concentrations were highest at the beginning of the study and decreased over time in most elephants.…”
Section: Discussionmentioning
confidence: 99%
“…Among blood biochemical parameters, creatine kinase (CK) is considered as the most important value related to training due to the fact that CK is the best indicator of striated muscle damage and most of its activity is in skeletal muscle 19 , 20 . The increase in plasma CK activity in dogs results from its leakage through the cell membrane and therefore, is evident in all conditions associated with muscle inflammation, necrosis, or degeneration but also after exhausting training 21 . Greyhounds have slightly higher CK activity than non-Greyhounds because of larger muscle mass 22 .…”
Section: Discussionmentioning
confidence: 99%
“…High plasmatic concentrations of these enzymes are due to the increased permeability and damages of the skeletal muscle cellular membranes, and they can be used to diagnose muscular pathological conditions. In healthy dogs their elevation can be temporary and may indicate a physiological response to intense exercise [ 23 , 27 , 28 , 29 , 30 , 31 ]. Two studies on search and rescue dogs [ 20 , 32 ], for example, reported increases in CK, AST and LDH due to exercise, but these parameters decreased to baseline after a rest of 30 min to 2 h. Different variables may affect the entity of the plasmatic elevations of these parameters, such as age, sex, breed and training [ 28 , 29 , 33 ].…”
Section: Discussionmentioning
confidence: 99%